1990
DOI: 10.1180/minmag.1990.054.375.02
|View full text |Cite
|
Sign up to set email alerts
|

Fluid inclusions in granulites and eclogites from the Bergen Arcs, Caledonides of W. Norway

Abstract: The Grenvillian granulite-facies complex on Holsn0y island, Bergen Arcs, W. Norway, has been metamorphosed at eclogite-facies conditions during the Caledonian orogeny (ca. 425 Ma). The granulite-eclogite facies transition takes place along shear zones and fluid pathways. Mineral thermobarometry indicates PT conditions of 800-900~ and 8-10kbar for the Proterozoic granulite facies metamorphism and 700-800 ~ and 16-19 kbar for the eclogite-forming event. Quartz in the granulite facies complex contains CO 2 fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This indicates that the granulite-facies overprinting on UHP eclogite followed isothermal decompression (Fig. Origin of N 2 Several studies have been made on eclogite containing N 2 -rich fluids, for example, in the Caledonides (Andersen, Burke & Austrheim, 1989;Andersen, Austrheim & Burke, 1990;Andersen et al 1993) and the Münchberg complex in Bavaria (Klemd, Van den Kerkhof & Horn, 1992), although fluids from eclogites from the Alps are chiefly aqueous brines without evidence of N 2 (Selverstone et al 1984;Philippot & Selverstone, 1991;Philippot, 1993). This type of high-density CO 2 is also reported from ultrahightemperature granulites from North China (Santosh et al 2008).…”
Section: C Source Of Fluidmentioning
confidence: 98%
“…This indicates that the granulite-facies overprinting on UHP eclogite followed isothermal decompression (Fig. Origin of N 2 Several studies have been made on eclogite containing N 2 -rich fluids, for example, in the Caledonides (Andersen, Burke & Austrheim, 1989;Andersen, Austrheim & Burke, 1990;Andersen et al 1993) and the Münchberg complex in Bavaria (Klemd, Van den Kerkhof & Horn, 1992), although fluids from eclogites from the Alps are chiefly aqueous brines without evidence of N 2 (Selverstone et al 1984;Philippot & Selverstone, 1991;Philippot, 1993). This type of high-density CO 2 is also reported from ultrahightemperature granulites from North China (Santosh et al 2008).…”
Section: C Source Of Fluidmentioning
confidence: 98%
“…1). Fluid inclusion data from several eclogites in the WGR and BAS suggest that the eclogite facies¯uids were both N 2 ±CO 2 ±H 2 O¯uids (Andersen et al, 1989(Andersen et al, , 1990(Andersen et al, , 1993 and brines (Andersen et al, 1993;Svensen et al, 1999). This bimodality in the composition of these¯uid inclusions has been recognized in other eclogite terranes as well (see Philippot et al, 1995, and references therein), but there is no systematic regional pattern in the distribution of the two types of inclusion¯uid in the WGR/ BAS.…”
Section: Geological Settingmentioning
confidence: 99%
“…However, several recent studies have demonstrated that many eclogites or other types of H P rock samples do contain workable, sometimes spectacular inclusions, many of them related to peak metamorphic conditions (e.g. Selverstone et al ., 1984, 1992; Andersen et al ., 1989, 1990; Klemd et al ., 1992, 1995; Nadeau et al ., 1993; Giaramita & Sorensen, 1994; Philippot et al ., 1995; Scambelluri et al ., 1997, 1998).…”
Section: Introductionmentioning
confidence: 99%